Phylogenetic Analysis of Wild Species and the Maternal Origin of Cultivars in the Genus Lilium Using 114 Plastid Genomes - Qing Duan; Qing Duan; Fang Liu; Daping Gui; Weishu Fan; Guangfen Cui; Guangfen Cui; Wenjie Jia; Wenjie Jia; Andan Zhu; Jihua Wang; Jihua Wang (Frontiers in Plant Science, 2022)
Lilies are one of the most important ornamental flowers worldwide with approximately 100 wild species and numerous cultivars, but the phylogenetic relationships among wild species and their contributions to these cultivars are poorly resolved. We collected the major Lilium species and cultivars and assembled their plastome sequences. Our phylogenetic reconstruction using 114 plastid genomes, including 70 wild species representing all sections and 42 cultivars representing six hybrid divisions and two outgroups, uncovered well-supported genetic relationships within Lilium. The wild species were separated into two distinct groups (groups A and B) associated with geographical distribution, which further diversified into eight different clades that were phylogenetically well supported. Additional support was provided by the distributions of indels and single-nucleotide variants, which were consistent with the topology. The species of sections Archelirion, Sinomartagon III, and Leucolirion 6a and 6b were the maternal donors for Oriental hybrids, Asiatic hybrids, Trumpet hybrids, and Longiflorum hybrids, respectively. The maternal donors of the OT hybrids originated from the two sections Archelirion and Leucolirion 6a, and LA hybrids were derived from the two sections Leucolirion 6b and Sinomartagon. Our study provides an important basis for clarifying the infrageneric classification and the maternal origin of cultivars in Lilium.